2013
DOI: 10.1292/jvms.12-0134
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection of <i>Leishmania donovani</i> DNA in a Stray Dog from a Visceral Leishmaniasis Endemic Focus in Bangladesh

Abstract: ABSTRACT. Although Phlebotomus argentipes as the only known vector of visceral leishmaniasis (VL) is zoophilic in nature, VL is considered to be anthroponotic in the Indian subcontinent. Peripheral blood samples from 85 stray dogs were examined for any molecular evidence of Leishmania infection in VL endemic areas of Bangladesh. Parasite DNA was detected in a blood sample from 1 of 85 (1.2%) stray dogs using ITS1-PCR, and PCR sequencing of the rRNA-ITS and cytochrome b gene confirmed that the parasitic DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…In a recent study, Leishmania DNA was detected in a single (1.2%) dog among 85 stray dogs using DNA extracted from whole blood spotted on filter paper. 14 We found that 20% and 10% of stray dogs were positive based on real-time PCR and PCR using buffy coat DNA, respectively, despite sampling from the same VL-endemic foci. The higher positive rate in our study probably reflects a higher assay sensitivity using buffy coat DNA than wholeblood preparations, as demonstrated in previous studies.…”
Section: Discussionmentioning
confidence: 68%
“…In a recent study, Leishmania DNA was detected in a single (1.2%) dog among 85 stray dogs using DNA extracted from whole blood spotted on filter paper. 14 We found that 20% and 10% of stray dogs were positive based on real-time PCR and PCR using buffy coat DNA, respectively, despite sampling from the same VL-endemic foci. The higher positive rate in our study probably reflects a higher assay sensitivity using buffy coat DNA than wholeblood preparations, as demonstrated in previous studies.…”
Section: Discussionmentioning
confidence: 68%
“…The most suspected animal reservoirs for L. donovani are dogs, which are known to play a key role as reservoir hosts in the transmission cycle of the closely related L. infantum [ 2 , 30 ]. Several authors have reported PCR-positivity or seropositivity of dogs in L. donovani foci [ 3 , 4 , 19 , 31 35 ], including Humera and Addis Zemen in Ethiopia [ 36 39 ]. In the present study, dogs demonstrated the highest Leishmania seroprevalence out of all the species tested at all study sites, with two PCR-positive dogs identified in Humera and Addis Zemen.…”
Section: Discussionmentioning
confidence: 99%
“…The first kala-azar (visceral leishmaniasis) patient was recorded in Jessore District of Bangladesh in 1824 (Ahluwalia et al, 2003). There are so many researches conducted in Bangladesh regarding VL but most of them for better non-invasive diagnostic methods in human (Alam et al, 1996). A significant number of human clinical case reports had also published .…”
Section: Introductionmentioning
confidence: 99%